Widowhood, Ex-Affinal Relationships, and Social Perceptions: A Case Study of Sundanese Muslim Women in Rural West Java, Indonesia - Mahira, Khansa; Mulyanto, Dede; Iskandar, Budiawati Supangkat (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2025)
This article explores the social perception of widows from an Islamic perspective, the various types of relationships between widows and their ex-affines, and the factors shaping these relationships among Sundanese Muslims in rural West Java. Employing a qualitative research design with a case study approach, the study engaged religious leaders and six widows who had diverse experiences with their ex-affinal kin. Data were collected through in-depth interviews and non-participant observations. The findings reveal that social perceptions of widows, as informed by Islamic teachings, are rooted in Qur’anic references; however, these teachings are not consistently reflected in actual practices within Cikembang Village. Instead, the findings align with existing literature on Muslim widows in other Southeast Asian contexts. The study identified three types of the widow–ex-affinal relationships: (1) positive—characterised by continued closeness, such as becoming friends or being regarded as a daughter; (2) negative—marked by hostility or estrangement, such as being treated as a hostile neighbour or stranger; and (3) neutral—defined by a distanced yet peaceful coexistence, such as simply being neighbours. Several factors influenced these relationship dynamics: (1) the nature of the previous personal bond, (2) the widow's age and adherence to cultural and religious principles, and (3) the birthplace of the deceased husband and the current residence of the in-laws. The classification of these relationships largely depended on the widow's post-marital situation and her interpretation of Islamic teachings. Overall, the findings offer valuable insights for developing culturally sensitive support systems for Muslim widows and contribute original perspectives to kinship studies in Southeast Asian anthropology. Specifically, this research sheds light on widow–ex-affinal relations within bilateral kinship systems—a context that remains underexplored in Indonesian Muslim communities.